Assessment of the Prevalence of Diabetes Mellitus Risk Cases Among Middle Age Group People - Nakka Surya Teja (International Journal of Community Health Nursing And Practices, 2024)
The cognizance of diabetes mellitus to humankind is as old as their own history of civilization. Description about diabetes is mentioned in Greek, Egyptian, Arabic, Chinese, and even in Indian medicine. Mellitus is a Latin word. The presence of a sweet taste in urine is employed to differentiate it from other poly uric conditions where glycosuria is not present. Diabetes is currently recognized as a diverse group of diseases characterized by chronic hypoglycemia, stemming from various underlying etiological factors, encompassing both environmental and genetic influences. Presently, over 70% of individuals with diabetes reside in low- and middle-income countries. It is estimated that 285 million people, constituting 6.4% of the global adult population, lived with diabetes in 2010. Among them, 20% of the current diabetic population were situated in the Southeast Asia region. The number of individuals with diabetes in these countries is anticipated to triple by the year 2025.
Keywords: Diabetes mellitus; Indian medicine; environmental and genetic influences; hypoglycemia